Формування та розвиток креативності студентів у процесі фахової підготовки у вищих навчальних закладах - П'явка, Катерина; Кузава, Ірина (My University, 2018)
У статті розглядається проблема розвитку креативності особистості та теоретично обґрунтовуються умови, які сприяють формуванню творчих здібностей та креативності.The article considers the problem of creativity development of a person and provides theoretical information about the conditions that contribute to the formation of creative abilities and creativity. The results of the theoretical analysis of the accumulated experience in psychology concerning studying creativity which indicates existence of creative potential in every child and the possibility of its development are presented in the article. The attention is drawn to the connection between creativity as a psychological process with other psychological processes. The special role of perception in the creative process is emphasized in the article as well as necessity of its development in childhood. The materials of research on problems of development of creativity are considered in the article. The article indicates the connection between creativity and such personal qualities as invention, originality, initiative, perseverance and working capacity. The factors of the environment that can have a positive and negative impact on the development of creativity are analyzed. The conditions which contribute to the formation of creativity of the individual are defined.
Keywords: креативність; creativity; творчі здібності; обдарованість; творчість; навчально-виховний процес; творча діяльність; студент; creative abilities; giftedness; creative work; educational process; creative activity; student